2011
DOI: 10.1016/j.cell.2011.03.021
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved F Box Regulatory Complex Controls Proteasome Activity in Drosophila

Abstract: Summary The Ubiquitin-Proteasome System catalyzes the degradation of intracellular proteins. Although ubiquitination of proteins determines their stabilities, there is growing evidence that proteasome function is also regulated. We report the functional characterization of a conserved proteasomal regulatory complex. We identified DmPI31 as a binding partner of the F-box protein Nutcracker, a component of an SCF ubiquitin ligase (E3) required for caspase activation during sperm differentiation in Drosophila. Dm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
167
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(177 citation statements)
references
References 53 publications
(80 reference statements)
9
167
1
Order By: Relevance
“…The PI31 FP domain mediates heterodimerization of SCF Fbxo7 and PI31. Consistent with this fi nding, the fl y homologue DmPI31 was found as a binding partner of the F box protein Nutcracker, a component of a SCF Ub ligase required for caspase activation during sperm differentiation in Drosophila (Bader et al , 2011 ). DmPI31 binds Nutcracker via a conserved mechanism that is also used by mammalian FBXO7 and PI31.…”
Section: Other Proteasome-interacting Proteins (Pips)supporting
confidence: 59%
“…The PI31 FP domain mediates heterodimerization of SCF Fbxo7 and PI31. Consistent with this fi nding, the fl y homologue DmPI31 was found as a binding partner of the F box protein Nutcracker, a component of a SCF Ub ligase required for caspase activation during sperm differentiation in Drosophila (Bader et al , 2011 ). DmPI31 binds Nutcracker via a conserved mechanism that is also used by mammalian FBXO7 and PI31.…”
Section: Other Proteasome-interacting Proteins (Pips)supporting
confidence: 59%
“…Recently, Steller's group found that fruit fly PI31, DmPI31, works in cooperation with 26S proteasomes (24,25). They showed that ectopic expression of DmPI31 suppressed an eye phenotype caused by proteasome dysfunction, whereas reducing DmPI31 function enhanced proteasome defects.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting reports as to the effect of PI31 on proteasome function. The original paper showed that mammalian PI31 inhibits 20S CP activity in vitro, but other reports indicate that PI31 cooperates with the proteasome in protein degradation in fruit flies (20,(24)(25)(26).…”
Section: Fub1 Is Associated Mainly With the 20s Cpmentioning
confidence: 99%
See 2 more Smart Citations